6x+x-0.9=6x+0.9

Simple and best practice solution for 6x+x-0.9=6x+0.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+x-0.9=6x+0.9 equation:


Simplifying
6x + x + -0.9 = 6x + 0.9

Reorder the terms:
-0.9 + 6x + x = 6x + 0.9

Combine like terms: 6x + x = 7x
-0.9 + 7x = 6x + 0.9

Reorder the terms:
-0.9 + 7x = 0.9 + 6x

Solving
-0.9 + 7x = 0.9 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-0.9 + 7x + -6x = 0.9 + 6x + -6x

Combine like terms: 7x + -6x = 1x
-0.9 + 1x = 0.9 + 6x + -6x

Combine like terms: 6x + -6x = 0
-0.9 + 1x = 0.9 + 0
-0.9 + 1x = 0.9

Add '0.9' to each side of the equation.
-0.9 + 0.9 + 1x = 0.9 + 0.9

Combine like terms: -0.9 + 0.9 = 0.0
0.0 + 1x = 0.9 + 0.9
1x = 0.9 + 0.9

Combine like terms: 0.9 + 0.9 = 1.8
1x = 1.8

Divide each side by '1'.
x = 1.8

Simplifying
x = 1.8

See similar equations:

| -3-6X=28 | | X+65X+1000=0 | | (18)-2y-4= | | 3/4x+2-5/4=-6 | | 13=2f-5 | | 6x+3-8x-16=0 | | 5x+7=-7x+43 | | 9t=4 | | -2(3x+1)-10=4 | | 5x+3=33-x | | 1/4x+4=-6 | | 2-x=-2x-12 | | 3x+5=-x+13 | | 3[4-2(x-1)]=3x+3 | | 5x+6=2x+27 | | -2/7y+3/7=2/5y+4/5 | | 18x-9=18x-9 | | 7y-4-4y-1= | | -7x+2=7x+156 | | 2+3x=5x+20 | | -x+9=-9 | | 1+4x=3x-10 | | 3ab^2*4a^2b^4=0 | | 1-6x=6x+133 | | 0=4x^2-1600x+174000 | | r^4-7r^2+6r=0 | | 3.6-3=2.6x | | -15x^2-11=0 | | 1x-8=-20+2x | | 0.05(60000-x)=5000 | | 2h^2+11h+5=0 | | 7x-12-9x+24=-6 |

Equations solver categories